PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN DI INDONESIA (Studi Empiris pada Perusahaan Finansial yang Terdaftar di Bursa Efek Indonesia pada Tahun 2014-2016) - Muhammad Hanif Risnanditya; Herry Laksito (Diponegoro Journal of Accounting, 2018)
This research aims to examine the impact corporate governance on firm performance of financial sector in Indonesia. Board independence, board size, independence of the audit committee members, number of financial experts in audit committee, number of audit committee meetings as independent variable for corporate governance. Firm performance as dependent variable is measured by ROA and Tobin’s Q value. Thie research uses government ownership, foreign ownership, size and leverage as a control variable.The population in this research are all financial companies listed in Indonesia Stock Exchange during the period 2014-2016. The sampling method in this research is purposive sampling with certain criteria. Total sample of this research is 202 companies.The result of this study showed that board independence, board size, number of financial experts in audit committee, number of audit committee meetings has positively significant to the firm performance, while board independence have negatively significant effect to the firm performance and independence of the audit committee members has not affected on the firm performance.